2021
DOI: 10.1109/jsen.2020.3035109
|View full text |Cite
|
Sign up to set email alerts
|

Power-Efficiency Evolution of Capacitive Sensor Interfaces

Abstract: Recent years have witnessed an improvement in the energy efficiency of capacitive sensor interfaces by more than three orders of magnitude. This paper reviews the architectural and circuit innovations that have contributed to this progress. The fundamental limit on the energy consumption of capacitive sensor interfaces is discussed, as well as the widely used figure-of-merit (FoM). Interfaces based on period modulation feature simple circuitry, but their power efficiency at higher resolution deteriorates. Thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Here, the capacitance reading circuit generally converts the variation in capacitance into a digital signal so that information can be easily processed in a subsequent digital system. Capacitance detection has two main techniques: (1) capacitance-to-time (C-T) transformation and (2) capacitance-to-voltage (C-V) transformation [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, the capacitance reading circuit generally converts the variation in capacitance into a digital signal so that information can be easily processed in a subsequent digital system. Capacitance detection has two main techniques: (1) capacitance-to-time (C-T) transformation and (2) capacitance-to-voltage (C-V) transformation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the capacitance reading circuit generally converts the variation in capacitance into a digital signal so that information can be easily processed in a subsequent digital system. Capacitance detection has two main techniques: (1) capacitance-to-time (C-T) transformation and (2) capacitance-tovoltage (C-V) transformation [6]. The capacitance-to-digital converter (CDC) using the C-T conversion technique is based on period modulation (PM) that converts the detected capacitance into different pulse width using oscillators [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many architectures of CDCs are demonstrated in the literature, exploiting the principles of phase/pulse modulation (PM) [ 3 , 4 , 5 , 6 , 7 ], modulation ( M) [ 8 , 9 , 10 ] and capacitive successive approximation register (CSAR) [ 11 , 12 , 13 , 14 , 15 ]. A detailed review of these techniques can be found in [ 16 ].…”
Section: Introductionmentioning
confidence: 99%